2012
DOI: 10.1002/ajp.21987
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Functionally Appropriate Tools by Capuchin Monkeys (Cebus apella)

Abstract: Capuchin monkeys (Cebus sp.) are notable among New World monkeys for their widespread use of tools. Like chimpanzees, they use both hammer tools and insertion tools in the wild to acquire food that would be unobtainable otherwise. Recent evidence indicates that capuchins transport stones to anvil sites and use the most functionally efficient stones to crack nuts. We further investigated capuchins' assessment of functionality by testing their ability to select a tool that was appropriate for two different tool-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Subjects and housing Subjects were seven brown capuchin monkeys (Cebus [Sapajus] apella; five females; mean age 8.43 + 3.51 years) and six squirrel monkeys (Saimiri sciureus; six females; mean age 10.17 + 3.49 years) housed in social colonies at Bucknell University. All subjects had extensive experience with manual cognitive testing (e.g., Judge & Bruno, 2012;Judge, Evans, Schroepfer, & Gross, 2011;Kurdziel & Judge, 2007;Marsh, Vining, Levendoski, & Judge, 2015;Zander & Judge, 2015) but not with quantity discrimination specifically. All subjects were tested alone in their home cage by temporarily closing off small sections of the housing area.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects and housing Subjects were seven brown capuchin monkeys (Cebus [Sapajus] apella; five females; mean age 8.43 + 3.51 years) and six squirrel monkeys (Saimiri sciureus; six females; mean age 10.17 + 3.49 years) housed in social colonies at Bucknell University. All subjects had extensive experience with manual cognitive testing (e.g., Judge & Bruno, 2012;Judge, Evans, Schroepfer, & Gross, 2011;Kurdziel & Judge, 2007;Marsh, Vining, Levendoski, & Judge, 2015;Zander & Judge, 2015) but not with quantity discrimination specifically. All subjects were tested alone in their home cage by temporarily closing off small sections of the housing area.…”
Section: Methodsmentioning
confidence: 99%
“…This requires an additional cognitive ability, as the individual must plan their action ahead of time. However, in previous tasks, capuchins have been able to select the correct tool in advance of being given access to an apparatus (Manrique et al, 2011) and have even been shown to travel 8 m to a different room to collect the appropriate tool after viewing an apparatus (Evans & Westergaard, 2004;Judge & Bruno, 2012). The planning involved in the two-trap task is no more demanding than in these previous tasks, and thus, is unlikely to be the only factor limiting their ability.…”
Section: Discussionmentioning
confidence: 99%
“…Although, as a group, the capuchin monkeys performed above chance, all 14 individuals failed to avoid the traps. The result was surprising, as there is strong evidence that capuchin monkeys can learn functional discriminations (Evans & Westergaard, 2004;Fujita et al, 2003Fujita et al, , 2011Judge & Bruno, 2012;Manrique et al, 2011;Painter et al, 2019;Sabbatini et al, 2014;Schrauf et al, 2008;Yocom & Boysen, 2010), with some evidence of this in squirrel monkeys (Painter et al, 2019). One explanation for their failure is the planning involved in the task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies with bonobos, orangutans, and chimpanzees, Mulcahy and Call (2006) and Osvath and Osvath (2008) observed that apes saved tools for future use. Contrary to this, macaques and capuchin monkeys did not spontaneously transport tools for future use but could be trained to do so (Bourjade, Thierry, Call, & Dufour, 2012;Dekleva, van den Berg, Spruijt, & Sterck, 2012;Judge & Bruno, 2012).…”
Section: Theory Of Mindmentioning
confidence: 96%